Implementasi Model Problem Based Learning dalam Pembelajaran Sains Anak Usia Dini di Taman Kanak-Kanak (TK) - Jf, Nurul Zahriani (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2018)
Basic competency to be achieved in early childhood science learning is to provide understanding, knowledge, thinking and curiosity skills, problem solving skills, and communication skills with what children need in their lives. At present there are still many teachers in early childhood education who lack understanding of science learning for children and difficulties in achieving these learning goals. Because it lacks the ability and / or mastery of the teacher in applying this learning to children. This study aims to contribute to how to implement Learning-based models in learning, in order to achieve learning objectives that are in accordance with the curriculum. The research method used is literature study. Learning in the literature on learning in early childhood and project-based learning learning models is then analyzed and explained by explaining how to implement it. The results of the study were obtained by implementing a problem-based learning model (problem-based learning model), so that some appropriate basic competencies can be obtained.